RESPON PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP BOKASHI KOTORAN SAPI DAN PUPUK ROCK FOSFAT PADA MEDIA GAMBUT - Raisa Baharuddin; Selvia Sutriana; Agus Albani (Jurnal Agrotek Tropika, 2024)
The development of shallot cultivation in Riau needs to be done by optimizing peatlands. However, problems such as low pH and low nutrient availability need to be addressed. The use of cow manure bokashi can increase the availability of soil nutrients and the addition of P fertilizer from rock phosphate is expected to increase the availability of P in peat soil. The purpose of this study was to determine the role of cow manure bokashi and rock phosphate fertilizer in increasing the production of shallot plants in peat media. This research was carried out at the UIR Experimental Garden, Pekanbaru, from September to December 2022. The materials used in this study were Brebes shallot seedlings, cow manure bokashi, rock phosphate, urea, KCl. The tools used in the research included hoes, tape measure, cutter knife, analytical scales, camera and stationery. The research method used a Factorial Completely Randomized Design (CRD). The first factor was the dose of cow manure bokashi with 4 treatment levels: without cow manure bokashi, 40, 80 and 120 g/polybag Bokashi cow manure. The second factor was the dose of rock phosphate fertilizer with 4 treatment levels: 0, 0.8 g/polybag, 1.6, 2.4 g/polybag. Each experimental unit was repeated 3 times. Observational data were analyzed statistically and further tested for HSD the 5% level. Application of cow manure bokashi with rock phosphate can increase shallot production. Application of cow manure bokashi 80 g/polybag with rock phosphate dose of 2.4 g/polybag increased the wet and dry shallot bulb weight.